THE EFFECT OF STEM-PjBL ON SEVENTH-GRADE STUDENTS' CREATIVE THINKING SKILLS IN LEARNING SUBSTANCES AND THEIR CHANGES - Annisa Fitria Rahayu; Muhyiatul Fadilah; Febri Yanto; Fatma Wati (Department of Science Education, 2026)
Creative thinking is one of the essential competencies required for learners in the twenty-first century. However, students' creative thinking skills remain relatively low in science learning. Preliminary observations conducted in a seventh-grade class at SMPN 1 Sijunjung revealed that students' creative thinking skills reached only 49%, indicating the need for more innovative instructional approaches. This study aimed to investigate the effect of STEM Project-Based Learning (STEM-PjBL) on seventh-grade students' creative thinking skills in the topic of Substances and Their Changes. A quasi-experimental research design employing a nonequivalent control group design was adopted. The participants were selected using purposive sampling, with one class assigned as the experimental group receiving STEM-PjBL instruction and another class serving as the control group receiving conventional instruction. Data were collected using an essay-based test designed to assess students' creative thinking skills. The collected data were analyzed using normality, homogeneity, and independent-samples t-tests. The results indicated no significant difference between the two groups on the pretest (p = 0.524 > 0.05), confirming comparable initial abilities. However, a statistically significant difference was found in the posttest scores (p = 0.005 < 0.05), indicating that students who learned through STEM-PjBL demonstrated significantly higher creative thinking skills than those who received conventional instruction. Therefore, it can be concluded that STEM Project-Based Learning has a significant positive effect on seventh-grade students' creative thinking skills in learning Substances and Their Changes.